Preparation of Oil-soluble Fe-Ni sulfide nanoparticles for Slurry-Phase hydrocracking of residue. (1st August 2022) - Luo, Hui; Sun, Jian; Deng, Wenan; Li, Chuan; Du, Feng
Highlights: Oil-soluble Fe-Ni sulfide nanoparticles were prepared and adopted as the catalyst for slurry-phase hydrocracking. FeNiSx exhibited excellent hydrocracking activity for converting VR into light oil at coke yield of 0.21 wt%. Mixed crystals of Fe and Ni sulfide were formed in FeNiSx . FeNiSx was uniformly dispersed in oil as spherical clusters with an average particle size of 338 nm. Abstract: Oil-soluble Fe-Ni sulfide nanoparticles (FeNiSx ) were prepared with a simple method and adopted as the catalyst for slurry-phase hydrocracking of Liaohe vacuum residue (LHVR) in this work. The results demonstrated that the FeNiSx particles exhibited excellent hydrocracking activity for converting LHVR into light oil with lower coke and gas formation, which were suppressed from 10.7 wt% to 0.2 wt% and from 9.6 wt% to 2.0 wt%, respectively, at 430 °C, 1 h, 7 MPa initial H2 and the FeNiSx dosage of 2000 μg/g. Especially the yield of light oil per unit of coke formation was significantly increased from 2.8 to 232.1, and the conversion of resin and asphaltene reached 62.9 wt% and 96.1 wt%, respectively. Furthermore, the sponge-type coke formed by using the FeNiSx particles is beneficial to suspend in the liquid product without deposition than the shot-type one produced by thermal cracking. The FeNiSx particles were characterized by FT-IR, XRD and Cryo-SEM to illustrate the possible relationship between the structure and activity. The characterization results indicated that Fe and Ni mixed crystals were formed in the FeNiSx particles, which were uniformly dispersed in the diesel as spherical clusters with an average particle size of about 338 nm because of the organic modified layer formed by oleic acid. The good solubility and dispersibility of the FeNiSx particles result in the excellent catalytic performance.